Energy dissipation in helicon plasma at the near field of an antenna - Olshansky, V. (Вопросы атомной науки и техники, 2018)
The results of a computer simulation of energy dissipation in helicon plasma at near field of an antenna are
presented. Results are reported for a double-half-turn antenna, and comparison is made to a double-saddle-coil
antenna which demonstrates the distinct inductive and helicon-wave modes. The computer simulation revealed a
significant wave-particle interaction in the near-field of the antenna that is less than half wavelengths from the
antenna. Namely, in addition to the ohmic heating from the currents induced by the helicon wave, electrons can
become trapped in the traveling helicon wave via the resonance condition. Представлено результати комп’ютерного моделювання дисипації енергії в геліконній плазмі в ближньому
полі антени. Результати наведені для «double-half-turn»-антени та порівнюються з «double-saddle-coil»-
антеною, яка демонструє різні індуктивні та геліконні хвильові моди. Комп’ютерне моделювання виявляє
суттєву взаємодію хвиля-частинка в ближньому полі антени на відстані менш ніж половина довжини хвилі
від антени. В додаток до омічного нагрівання струмом, що індукується геліконною хвилею, електрони
можуть бути захопленими геліконною хвилею, що розповсюджується, при наявності резонансу. Представлены результаты компьютерного моделирования диссипации энергии в геликонной плазме в
ближнем поле антенны. Результаты даны для «double-half-turn»-антенны и сравниваются с «double-saddlecoil»-антенной, которая демонстрирует различные индуктивные и геликонные волновые моды.
Компьютерное моделирование обнаруживает существенное взаимодействие волна-частица в ближнем поле
антенны на расстоянии менее половины длины волны от антенны. В дополнение к омическому нагреву
током, индуцированным геликонной волной, электроны могут захватываться распространяющейся
геликонной волной при наличии резонанса.